VD_FINDINFO HC / 2013 / 41 vom 27. Dezember 2012 - VD Tribunal cantonal (2012)
PREUVE À FUTUR, DROIT D'ÊTRE ENTENDU | 158 al. 1 CPC (CH), 158 al. 2 CPC (CH), 248 let. d CPC (CH), 319 let. b ch. 2 CPC (CH)